2018
DOI: 10.5430/rwe.v9n2p44
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of International Public Sector Accounting Standards in Public Sector of Developing Economies -Analysis of Five South Asian Countries

Abstract: We examined the extent of adoption of the International Public Sector Accounting Standards (IPSAS) in South Asia and the challenges that are decelerating this process. The moderating organization, International Public Sector Accounting Standards Board (IPSAB), instituted IPSAS in an effort to improve financial reporting by public sector organizations and for comparability purposes. The aims of this research were to establish to what extent the IPSAS has been adopted in South Asia and determine the drawbacks co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, their existence was deemed as hindering rather than supporting such adoption. These views align with (Wang and Miraj 2018;Khdir and Białek-Jaworska 2020;El-Helaly et al 2020) that the weaker institutions and politicians, obstacles to infrastructure, and infrastructure corruption would impair the foreign investments inflow in greater ways than the adoption of international harmonised standards.…”
Section: Foreign Corporations and The International Accounting Firmsmentioning
confidence: 59%
“…Therefore, their existence was deemed as hindering rather than supporting such adoption. These views align with (Wang and Miraj 2018;Khdir and Białek-Jaworska 2020;El-Helaly et al 2020) that the weaker institutions and politicians, obstacles to infrastructure, and infrastructure corruption would impair the foreign investments inflow in greater ways than the adoption of international harmonised standards.…”
Section: Foreign Corporations and The International Accounting Firmsmentioning
confidence: 59%
“…It had positive impact through enhanced efficiency, effectiveness, accountability and allowed for better costing of programmes and services provided by government (Patrick, Danladi, Caleb, & Linda, 2017). But, it is found that some common challenges are faced by nations in South Asia in the adoption of IPSAS standards such as lack of experienced staff, inadequate change management structures, failure by the governments to institute professional committees to oversee the reforms, and inconsistencies in the adoption process by the individual public entities (Wang & Miraj, 2018). Accounting reforms, and its internal and external financial control systems give an impulse to all managerial fields -strategic management, human resources management, management by objectives, etc.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is a significant step by these departments for strengthening the accounting system and proper fund management for getting positive support to fulfil shortages of funds as much as possible and for minimising deficits of funds for the State. It may be mentioned here that the PIRSA System was implemented by the author of this paper when he was working in those departments as an AO 15 at FCS&CA Department, and OSD (Finance) 16 at DHE and TTAADC in addition to his ongoing academic service.…”
Section: Tripura Tribal Areas Autonomous District Council (Ttaadc)mentioning
confidence: 99%
“…However, the possible benefits must be compared to the costs of implementation, such as personnel, training and consulting and ICT costs (Grossi and Pepe, 2009; Heald and Georgiou, 2000; Hepworth, 2017). In addition to resource and knowledge barriers (Wang and Miraj, 2018; Adebisi et al. , 2019), institutional barriers (Robb and Newberry, 2007; Oulasvirta, 2014) must also be anticipated.…”
Section: Literature Review and Basic Conceptsmentioning
confidence: 99%